An Analysis of Sexual Abuse Committed by a Kiyai Against Santri (A Case Study at Islamic Boarding School X, Meranti Islands) - Askarial; Wan Arash Nirwanda (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
This research aims to analyze sexual abuse committed by a kiyai (Islamic religious leader) against a santri (Islamic boarding school student) at Islamic Boarding School X in the Meranti Islands. The background of the case highlights how positions of authority within religious institutions can be misused for personal gratification. The study uses a qualitative case study method with a criminological approach. Data were collected through documentation, interviews, and observation. The findings show that the perpetrator used his religious status to manipulate and exploit the victims psychologically and sexually. The factors contributing to this abuse include power imbalance, blind obedience of students, lack of supervision, and the closed nature of boarding school environments. The impact on victims includes psychological trauma, loss of trust, and long-term emotional disturbances. This research recommends stronger regulatory oversight of religious educational institutions and emphasizes the need for safe reporting mechanisms and awareness education to prevent abuse within pesantren environments.